Finite Element Modeling Of Subsidence Induced By Underground Coal Mining: The Influence Of Material Nonlinearity And Shearing Along Existing Planes Of Weakness - Daniel W. H. Su (International Conference on Ground Control in Mining, 1990)
Surface subsidence induced by multiple-panel coal extraction was calculated with finite element stress analysis. The use of nonlinear material behavior and GAP elements, which provide a realistic representation of shearing along existing planes of weakness, allows the finite element program to accurately reproduce observed subsidence profiles. A reduction factor of 1/6 is applied to the measured rock strength and modulus for use in the finite element model. The models satisfactorily predict a significant change in maximum subsidence and subsidence profile associated with an increase from subcritical to near critical panel width. Modeled shearing along planes of weakness is in good agreement with available time domain reflectometry field observations and is demon¬strated to have a very profound effect on the maximum subsidence and the shape of the subsidence profile. When both material nonlinearity and planes of weakness are incorporated, the finite element model appears to possess great potential for accurately predicting surface subsidence and subsurface strata deformation in environments where little subsidence information is available.